A Computional Study On Influence Of Circular Perforation In Web On Structural Capacity Of Reinforced Concrete Sheet Piles - Marcdo, Jong Min Inn (Universiti Sains Malaysia, 2019)
Sheet piles are one type of earth retaining structures which provide support against lateral earth pressure. Sheet piles have wide application in slope protection and road embankments. In Malaysia, precast concrete is the most common IBS component. Precast reinforced concrete sheet piles are manufactured with corrugated cross section and a pile head for easy installation using vibro hammer. The main objectives of this study are to study the effect of clear spacing between perforations and diameter of the perforation on the web section of sheet piles and compare the structural capacity of sheet pile with perforated web and without perforated web. Finite element analysis was carried out using finite element software ANSYS and LUSAS. A total of 26 models consisting 5 different clear spacing between perforation and 5 different diameters of perforation together with a controlled model have been considered. From the analysis, it can be concluded that that the larger the total area of perforation at the web section, the higher the reduction of structural capacity of the concrete. The total area of perforation is governed by two factors, which are diameter of perforation and clear spacing between perforation. The maximum reduction in bending moment at first crack and the corresponding deflection relative to the control model are 52.12 % and 7.702% respectively.